Bar-spiral interaction induces radial migration and star formation bursts - Marques, Lea; Minchev, I.; Ratcliffe, B.; Khoperskov, S.; Steinmetz, M.; Wenger, T. V.; Buck, Tobias; Martig, M.; Kordopatis, G.; Schultheis, M.; Zucker, D. B. (Astronomy and astrophysics, 2025)
Context: Central bars and spirals are known to impact significantly the evolution of their host galaxies, both in terms of dynamics and star formation. Their typically different pattern speeds cause them to regularly overlap, which induces fluctuations in bar parameters. Aims: In this paper, we analyze both numerical simulations of disk galaxies and observational data to study the effect of bar-spiral physical overlap on stellar radial migration and star formation in the bar vicinity, as a function of time and galactic azimuth. Methods: We studied three different numerical models, two of which are in a cosmological context, alongside APOGEE DR17 data and the WISE catalog of Galactic HII regions. Results: We find that periodic boosts in stellar radial migration occur when the bar and spiral structures overlap. This mechanism causes net inward migration along the bar leading side, while stars along the bar trailing side and minor axis are shifted outward. The signature of bar-spiral-induced migration is seen between the bar inner Lindbald resonance and well outside its corotation, beyond which other drivers take over. We also find that, in agreement with simulations, APOGEE DR17 stars born at the bar vicinity (which are mostly metal rich) can migrate out to the solar radius while remaining on cold orbits. For the Milky Way, 13% of stars in the solar vicinity with an eccentricity <0.5 were born inside the bar, compared to 5-20% in the simulations. Bar-spiral reconnections also result in periodic starbursts at the bar ends with an enhancement of up to a factor of 4, depending on the strength of the spiral structure. Similarly to the migration bursts, these do not always happen simultaneously at the two sides of the bar, which hints at the importance of odd spiral modes. Data from the WISE catalog suggest this phenomenon is also relevant in our own Galaxy.